Community-forming traits play role in effective colonization of plant-growth-promoting bacteria and improved plant growth - Pathak, Devashish; Suman, Archna; Sharma, Pushpendra; Aswini, Krishnan; Govindasamy, Venkadasamy; Gond, Shrikant; Anshika, Rana (Frontiers in Plant Science, 2024)
Community forming traits (CFts) play important role in the effective colonization of plant growth promoting bacterial communities that influence host plants positively by modulating their adaptive functions. In this study by considering plant growth promoting traits (PGPts) and community forming traits (CFts), three communities were constructed viz. SM1 (PGPts), SM2 (CFts), and SM3 (PGPts+CFts). Each category isolates were picked up on the basis of their catabolic diversity of different carbon sources. Results revealed a distinctive pattern in the colonization of the communities possessed with CF traits. It was observed that the community with CFts colonized inside the plant in groups or in large aggregations, whereas the community with only PGPts colonized as separate individual and small colonies inside the plant root and leaf. The effect of SM3 in the microcosm experiment was more significant than the uninoculated control by 22.12%, 27.19% and 9.11% improvement in germination percentage, chlorophyll content and plant biomass, respectively. The significant difference shown by the microbial community SM3 clearly demonstrate the integrated effect of CFts and PGPts on effective colonization vis-à-vis positive influence on the host plant. Further detailed characterization of the interaction will take this technology ahead in sustainable agriculture.